Case Report: Successful management of severe suicidal lamotrigine overdose-induced status epilepticus with sustained low-efficiency dialysis - Kawahara, Naoki; Matsui, Hiroki; Morishita, Koji (Frontiers in Toxicology, 2025)
IntroductionLamotrigine, a common antiepileptic, typically has a favorable safety profile. However, an overdose can lead to severe central nervous system complications, including refractory status epilepticus. The optimal management of severe overdose with refractory status epilepticus remains uncertain, and the role of extracorporeal removal methods, such as blood purification, has not been fully established.Case DescriptionA 20-year-old female with bipolar disorder presented with altered consciousness and status epilepticus 7 h after ingestion of 4.9 g of lamotrigine. As a case of lamotrigine intoxication, initial management with gastric lavage, activated charcoal, benzodiazepines, and levetiracetam failed to control the seizures, and the patient required continuous midazolam and ventilation. Slow low-efficiency dialysis (SLED) was initiated 18 h after admission. Lamotrigine levels substantially decreased from 33.9 to 13.5 μg/mL within 5 h post-SLED, representing a 60.2% reduction. The patient showed marked neurological improvement, with seizure cessation, allowing for discontinuation of midazolam. She was extubated on day 4 and discharged on day 7 with full recovery.DiscussionThis case highlights the successful use of SLED in severe lamotrigine overdose-induced refractory status epilepticus. The correlation among SLED use, reduced lamotrigine levels, and clinical improvement suggests that blood purification may be beneficial in severe toxicity, especially in patients with status epilepticus. This adds to the evidence supporting blood purification for accelerated drug removal and improved outcomes in select severe cases. Prompt recognition of this potentially life-threatening condition and consideration of intensive care, including blood purification, are vital for successful management.